History and Structure of the Fourth Leading Emergency Medical Service in the World; a Review Article - shakeri, khosro; Jafari, Mehdi; Khankeh, Hamidreza; Seyedin, Hesam (Archives of Academic Emergency Medicine, 2019)
Over forty-three years have passed since the foundation of pre-hospital emergency care system in Iran. Considering the changes that have taken place in recent years in pre-hospital emergency and limited studies in this area, the present review aimed to describe the history, organizational structure, combination of workforce, dispatch system, medical direction and innovations in the pre-hospital system of Iran. Â The present paper also discusses the strengths and weaknesses of the current system.